The similarity analysis of Port State Control regimes based on the performance of flag states. (May 2020) - Emecen Kara, Esma Gül; Okşaş, Olgay; Kara, Gökhan
Port State Control inspections play a paramount role in the enhancement of maritime safety. Port State Control regimes were established to ensure sustainability of Port State Control inspections. There are a total of 10 Port State Control regimes. Although all of these Port State Control regimes inspect foreign flag ships calling on their ports in compliance with international maritime safety and pollution regulations, still different implementations exist between these Port State Control regimes. According to the detentions, 73% of flag states have different performances in Port State Control regimes. However, the uniformity in inspections and detentions is quite important in the improvement of the effectiveness of Port State Control inspections in the world. This study aims at assessing the similarities between the Port State Control regimes on the basis of the performance of flag states as regards their Port State Control inspections. The similarities of the Port State Control regimes are analyzed employing the hierarchical clustering method using the detention and deficiency rates similarity matrices, the risk levels similarity matrices of flag states, and the combined similarity matrix. Accordingly, similarities between Port State Control regimes are discussed relative to each other and the Paris memorandum of understanding.